Biostimulant Effect and Antioxidant Responses of Carrot Extract and the Viability of Rice Seeds Under Salt Stress - Sheila Bigolin Teixeira; Stefânia Nunes Pires; Caroline Hernke Thiel; Cristiane Deuner; Diogo da Silva Moura; Natalia da Silva Garcia; Filipe Selau Carlos; Fernanda Reolon de Souza; Te Ming Tseng; Sidnei Deuner (Seeds)
Bioactive compounds in plants, such as carrots, have been widely used for their benefits. In agriculture, their potential as biostimulants still needs to be investigated, especially for their possible antioxidant action in plants subjected to abiotic stresses, such as salinity. This work aimed to evaluate the elicitor potential of carrot extract in alleviating salt stress in rice plants. This study aimed to evaluate the elicitor potential of carrot extract in alleviating saline stress in the rice cultivars BRS Querência and BRS 358. Aqueous extracts of carrot roots at concentrations of 0% (water), 25%, 50%, and 100% were used to soak rice seeds for 48 h, which were then subjected to different concentrations of NaCl (0, 25, 75, and 150 mM). To determine the effect of carrot extract as an elicitor under saline stress conditions, the following tests were conducted: germination, seedling length, dry mass, and oxidative stress through the activity of antioxidant enzymes, superoxide dismutase (SOD), ascorbate peroxidase (APX), catalase (CAT), peroxide content, and lipid peroxidation (hydrogen peroxide H2O2 and malonaldehyde MDA). Carrot extract increased the germination rate and maintained germination even under increased salinity rates in both cultivars. The application of 25 mM NaCl also boosted germination rates, followed by a significant decrease due to increased salinity rates. Shoot and root lengths and dry mass parameters showed a linear decrease in response to increasing NaCl concentrations. The activities of superoxide dismutase (SOD), ascorbate peroxidase (APx), and catalase (CAT) enzymes tended to decrease as the concentration of carrot extract increased, whereas the opposite was observed with NaCl application. Based on the combined analysis of the evaluated parameters, carrot extract application under the tested conditions was efficient in mitigating oxidative stress caused by high salinity conditions.